INDONESIAN STUDENTS MISCONCEPTION IN USING PRESENT PERFECT TENSE TO WRITE COMPOSITION - Syaifur Rochman (Celt: A Journal of Culture, English Language Teaching & Literature, 2003)
This article describes a research on the error analysis in the uses of present peifect tense made by freshmen studying at English Department in "Universitas lenderal Soedirman (UNSOED). It investigates the students' mistakes in using the present pelfect forms when writing composition. The result shows that most rejpondents still had difficulties in applying present perfect into sentences appropriately. This is mainly due to the respondents' lack of understanding on what the present peifect means. This suggests that students should improve their understanding on the present perfect given to its common use both in written and spoken English.